Storytelling to teach literacy: The implementation in an EFL classroom - Satriani, Intan (Universitas Merdeka Malang, 2021)
Storytelling can become a part of literacy practice. It improves children listening skills, increases language appreciation, and more thoughtful organization in their writing. On the point of that, this research aims to find out stages in implementing storytelling in teaching literacy. The research employed a qualitative case study research design. This method was used to investigate the phenomenon which is seen from the participants’ point of view. In line with that definition, this research was conducted to explore how storytelling can develop the literacy ability of second-grade students of junior high school. The data were collected through classroom observations and students’ writing products. The findings obtained that the teaching program which was conducted in seven units was successful to develop students’ literacy ability. Mainly, they showed some improvement in reading comprehension and interest. Besides, they showed their development in writing especially schematic structure, grammar roles, and graphic features. DOI: 10.26905/enjourme.v6i2.6433